Analysis and Development of an Online Knowledge Management Support System for a Community of Practice - Mafereka, Moeketsi (Department of Electrical Engineering, 2020)
The purpose of this study was to investigate how particular business practices, focusing on those occurring in multi-site non-governmental organization (NGOs), could be enhanced by use of a knowledge management system (KMS). The main objective of this KMS is to enhance business processes and save costs for a multi-site NGO through streamlining the organizational practices of knowledge creation, storage, sharing and application. The methodology uses a multiple perspective approach, which covers exploration of the problem space and solution space. Under exploration of problem space, interviews with employees of the NGO are done to identify core problem that the organization faced. Still under exploration of problem space, organization’s knowledge management maturity was assessed through an online questionnaire. The methodology then moved on to exploration of problem space. During the exploration of problem space, the requirements gathering and definition process was done through a combination of interviews with company employees and by completing a systematic literature review of best practices. The requirements were used to design system architecture and use-case models. The prototype for a Community of Practice (COP) support website was developed and investigated in test cases. The tests showed that the prototype system was able to facilitate asynchronous communication through the creation and management of events, creation and management of collaboration groups, creation of discussion topics and creation of basic pages. Furthermore, security capabilities were tested in terms of login functionality. Lastly page load times were tested for eight different scenarios. The system performance was found to be satisfactory because the scenarios covering crucial system requirements aspects had a response time of below 11 seconds. An exception was the landing page, which after login took 26 seconds to load. It is believed that creation of a platform that enables, and records, user interaction, easy of online discussions, managing groups, topics and events, are all major contributors to a successful knowledge management approach.